1996
DOI: 10.1148/radiology.200.1.8657946
|View full text |Cite
|
Sign up to set email alerts
|

Liver tumors: comparison of MR imaging with Gd-EOB-DTPA and Gd-DTPA.

Abstract: Gd-EOB-DTPA-enhanced MR imaging enables improved detection of hepatic lesions over Gd-DTPA-enhanced MR imaging while providing comparable differential diagnostic information.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

19
290
0
6

Year Published

1999
1999
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 445 publications
(315 citation statements)
references
References 0 publications
19
290
0
6
Order By: Relevance
“…Gadoxetic acid can effectively be used in dynamic and liver-specific static MRI with accurate delineation, classification, and characterization of liver tumors, in which excellent sensitivity and characterization for hepatocellular lesions are provided (10,12,14,(16)(17)(18)(19). The diagnosis of early HCC is one of the potential indication (20,21). Decreased signal intensity on hepatocyte-phase is strongly correlated with carcinogenesis of HCC (22).…”
Section: Discussionmentioning
confidence: 99%
“…Gadoxetic acid can effectively be used in dynamic and liver-specific static MRI with accurate delineation, classification, and characterization of liver tumors, in which excellent sensitivity and characterization for hepatocellular lesions are provided (10,12,14,(16)(17)(18)(19). The diagnosis of early HCC is one of the potential indication (20,21). Decreased signal intensity on hepatocyte-phase is strongly correlated with carcinogenesis of HCC (22).…”
Section: Discussionmentioning
confidence: 99%
“…In several clinical studies, this contrast agent has been demonstrated to provide differential diagnostic information comparable to nonspecific gadolinium chelates (8,14) and to improve the detection of focal liver lesions due to its highly specific uptake by hepatocytes (20). In addition, Gd-EOB-DTPA allows assessment of arterial perfusion during the vascular phase of dynamic imaging, and may be adapted to the other abdominal organs as well as liver, such as with Gd-DTPA.…”
Section: Discussionmentioning
confidence: 99%
“…These results may indicate that Gd-EOB-DTPA affects the enhancement effect in the arterial phase of various tumors, especially of hypervascular tumors such as hepatocellular carcinoma and renal cell carcinoma (8). Further clinical studies in patients with various tumors are needed to clarify the influence of less enhancement effect of Gd-EOB-DTPA in the arterial phase on MR diagnosis for solid tumors, especially with hypervascularity.…”
Section: Figurementioning
confidence: 98%
“…13,14 The approved package insert dose of gadoxetic acid, 0.025 mmol/kg, yields a quarter of the dose of gadolinium of traditional formulation agents, including gadopentetate dimeglumine, gadoteridol, gadodiamide, gadoversetamide, and gadobenate dimeglumine. 15 This dose was determined based on preclinical studies 16,17 that demonstrated comparable early enhancement of hypervascular tumors between MRI with a 0.025 mmol/kg dose showed comparable early enhancement of hypervascular tumors to gadopentetate dimeglumine 16 A dose of 0.025 mmol/kg was also found to be the minimum effective dose during the hepatobiliary phase for the detection and characterization of lesions. 17 However, the imaging sequences used in these studies (both published in 1996) are no longer routinely used in clinical MR imaging.…”
Section: Introductionmentioning
confidence: 99%